Sistem Informasi Pencatatan Kas Masuk Pada Lemon Fresh Laundry Jambi - Darmuji; Anjar Febriansyah (LP2M Politeknik Jambi, 2021)
Laundry business is a business related to laundry services with washing machines and automatic dryers and special cleaning and fragrance fluids. This business is mushrooming in big cities where there are many boarding houses and rented houses, where renters of boarding or rented houses do not have time or cannot do their own washing and ironing of clothes due to busyness as students and workers. Lemon Fresh Laundry, one of the kilogram laundry in Kisaran. Its strategic location, precisely on Jl. Lkr. Barat 3, Bagan Pete, Kec. Kota Baru, Jambi City, makes many customers visit every day to use Lemon Fresh Laundry services. Until now Lemon Fresh Laundry does not have its own information system and still uses a manual system, this laundry also does not have an accurate database storage system so that all data is still stored in a book. With the use of this manual system, various problems arise such as the difficulty of finding customer data in a book. The purpose of this Web-based cash-in recording system application is to provide professional services to customers and minimize errors that may occur. This Web-based cash recording information system uses ERD and MYSQL flow diagrams for data processing.